Analisis Pengaruh Jenis Tanah Terhadap Kerusakan Jalan Kota Semarang Berbasis Sistem Informasi Geografis - Andreas Ardianto Prodjo Koesoemo; Andri Suprayogi; Hani'ah . . (Jurnal Geodesi UNDIP, 2014)
Condition of roads in an area influenced by the type of soil that is underneath. An area generally have different soil types. Different soil types will have different levels of hardness. With the variety of soil types of an area will affect the state of development in the region. It also affects the condition of the road.This research was conducted in the districts of North Semarang, Semarang Central, South Semarang, West Semarang and East Semarang. This study was conducted to determine the distribution of road damage to the soil type in the study site using a Geographic Information System, which provides the function of roads, road conditions, street paving types, and soil types.Research in 2012 showed more road damage occurring on alluvial soil types at 15481.492 meters. Based on the research that has been done can be concluded road damage occurs in many types of soil that is soft and hardening unfavorable road.  Keywords : Geographic Information Systems , Damage Roads , Soil Type